1960
DOI: 10.1021/ac60165a004
|View full text |Cite
|
Sign up to set email alerts
|

Polarographic Determination of Metal Driers in a Nonaqueous Solution

Abstract: ure 1 is a polarogram of a solution containing 3.76 X 10~4M arsenic as arsenite ions, whereas curve B is a polarogram of the same solution but without arsenic. The increase in current of the solution containing the arsenite ions occurred earlier along the voltage axis than the solution containing no arsenite. This difference may indicate that the arsenite ions wrere reduced in this medium but that the polarographic wave was not formed because of the early reduction of the sodium ions present in the supporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1962
1962
1985
1985

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…The formation of the intermediate ketyl in the reduction of benzophenone has been demonstrated by large scale electrolysis in dimethylformamide (815), and by cyclic voltammetry in alkaline aqueous alcohol solutions (387). This intermediate has also been detected in photochemical reductions (72,73).…”
Section: Systemsmentioning
confidence: 95%
See 1 more Smart Citation
“…The formation of the intermediate ketyl in the reduction of benzophenone has been demonstrated by large scale electrolysis in dimethylformamide (815), and by cyclic voltammetry in alkaline aqueous alcohol solutions (387). This intermediate has also been detected in photochemical reductions (72,73).…”
Section: Systemsmentioning
confidence: 95%
“…Other studies found that the peroxidic content of benzene extracts of corn was increased by ultrasonic vibrations (185) and that the peroxides in menhaden oil interfered in the estimation of iron (387). Sulfur Compounds.…”
Section: Systemsmentioning
confidence: 99%